Stimulasi Kemampuan Anak Usia Dini dalam Mengenal Huruf melalui Media Kartu (Suatu Kajian Literatur) - Juwariyah, Juwariyah; Wahyuni, Eka Sri; Vebrianti, Lina; Utami, Tri; Suharlina, Suharlina; Febriyanto, Dedi (Lembaga Yasin AlSys, 2022)
The purpose of writing this article is to describe the stimulation of children's ability to recognize letters through card media. In this study the method used is descriptive qualitative method which is a literature study. Researchers use various written sources such as books, articles, journals, theses and documents that are relevant to the research in this study. In the study of this research literature, there was an increase in Children's Ability to Recognize Letters through the media of theme cards in early childhood learning. Learning in this study focuses on card media in improving children's ability to recognize letters. The results of several card media studies can improve children's ability to recognize letters and read in children, through themes that are taught in every school. Playing or games is the right way to develop early childhood language skills, especially in letter recognition. The learning atmosphere can be realized in a letter guessing game using card media, which makes children feel happy and not boring.